GENERAL CHARACTERISTICS OF LYMPHOID TISSUE ASSOCIATED WITH THE MUCOUS MEMBRANES OF THE DIGESTIVE SYSTEM - Hryn, Volodymyr; Kostylenkо, Yuriy; Maksymenko, Oleksandr; Svintsytska, Nataliia; Tykhonova, Olesia; Tarasenko, Yana; Prysyazhnyi, Denys (Eastern Ukrainian Medical Journal, 2025)
Introduction. Lymphoid tissue associated with the mucous membranes of the digestive system plays an important role in the functioning of the immune system, acting as the body's first line of defense against external pathogens. Considering that the digestive system is one of the main routes of entry into the body of both beneficial and pathogenic microorganisms, the mechanisms of immune protection in this region should be as effective and adapted as possible. It is the presence of a branched structure of mucosa-associated lymphoid tissue (MALT), which includes tonsils, solitary and aggregate lymphoid nodules, in particular Peyer's patches, that ensures timely immune control and tolerance to obligate microflora. The study of the structure, functions, and interactions of lymphoepithelial formations with pathogens and commensals is important for understanding the pathophysiology of many diseases associated with immunodeficiency or immune aggression, as well as for the development of new approaches for the treatment and prevention of infectious and autoimmune diseases of the digestive system.Methods. An analytical review was carried out on the basis of own research and peer-reviewed articles, monographs, textbooks. A literature search on the anatomical and functional characteristics of lymphoid tissue associated with the mucous membrane of the digestive system was carried out using the electronic databases PubMed, Google Scholar and the scientific library of the Poltava State Medical University.Results. Studies have shown that the structured lymphoid formations of the mucous membranes of the digestive system are important components of barrier protection, which is formed during ontogenesis and is activated after birth. Lymphoepithelial formations of the intestines have a high concentration in the caudal direction, which coincides with the growth of the concentration of microflora that adapts in this environment. It was found that single lymphoid nodules and Peyer's patches were located in critical areas of the intestine where there was close contact with commensal and pathogenic microorganisms. Lymphoid nodules did not have a connective tissue capsule, but the cells of lymphoid tissue were grouped according to the type of reticular tissue, which allowed rapid activation of immune mechanisms. An important component was also the presence of follicle-associated epithelium, which provided a protective function and served as a barrier for pathogens.Conclusion. Thus, the lymphoid tissue of the digestive system, integrated into the epithelial structures, forms a complex immune barrier, which is an important part of the mucosa-associated lymphoid tissue. Lymphoepithelial formations, as the data show, are adapted to control the microflora and ensure tolerance to commensals, which indicates their evolutionary significance. The results of the study confirm that the structured lymphoid formations of the mucous membranes of the digestive system are important not only for the physiology of digestion, but also for the maintenance of immune homeostasis, and also open the prospects for further research in order to develop new therapeutic strategies for the treatment of immune disorders of the digestive tract.